2013
DOI: 10.1155/2013/878295
|View full text |Cite
|
Sign up to set email alerts
|

A Validated Stability-Indicating RP-HPLC Method for the Simultaneous Determination of Tenofovir, Emtricitabine, and a Efavirenz and Statistical Approach to Determine the Effect of Variables

Abstract: A simple, rapid, and stability-indicating RP-HPLC method for a combination of tenofovir disoproxil fumarate (TDF), emtricitabine (FTC), and efavirenz (EFV) was developed and validated with the help of a suitable statistical software as an application tool for the quality by design. The drugs individually, and in combination, were subjected to forced degradation (thermal, photolytic, hydrolytic, and oxidative stress conditions) and accelerated stability studies (40 ± 1°C/75 ± 3% RH for three months). Successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Wavelength of maximum absorption for 10 µg/mL solution of the bulk drug in methanol was scanned using UV-Visible spectrophotometer within the range of 200-400 nm wavelength with methanol as reference. The absorption curve shows at 228 nm for atenolol formulation [11][12][13][14][15][16] .…”
Section: Determination Of Working Wavelength (λMax)mentioning
confidence: 99%
“…Wavelength of maximum absorption for 10 µg/mL solution of the bulk drug in methanol was scanned using UV-Visible spectrophotometer within the range of 200-400 nm wavelength with methanol as reference. The absorption curve shows at 228 nm for atenolol formulation [11][12][13][14][15][16] .…”
Section: Determination Of Working Wavelength (λMax)mentioning
confidence: 99%
“…Few methods based on HPLC technique were reported to quantify ETC, EVR and TNF combination, (Devrukhakar et al, 2013;I H T Guideline, 2005) , (Ramaswamy and Dhas, 2018) , (Palavan et al, 2013) , (Rezaei et al, 2019) , (Raju et al, 2008) , (Varma et al, 2014) , Atlas et al (2016) . UPLC is a signi icant laboratory technique that reduces costs and improves the analytical performance needed to develop and validate the process.…”
Section: Introductionmentioning
confidence: 99%
“…Literature indicates spectrophotometry [5][6][7][8][9][10][11] , HPLC [12][13][14][15] , HPTLC 16 and LC/MS/MS 17 methods for determination of TDF individually and in combination with other drugs in pharmaceutical formulations, drug substance, and biological matrices. Similarly for EMT individually and in combination with other drugs by UV 18,19 , HPLC in pharmaceutical formulations, drug substance and biological matrices [20][21][22][23][24][25] , HPTLC, LC/MS/MS 26 and stability indicating liquid chromatographic methods 27 were reported. A detailed literature survey for RPV revealed that few analytical methods are available using spectrophotometric 28 , HPLC 29 and HPTLC 30 , individually.…”
Section: Introductionmentioning
confidence: 99%